Study of clinical profile and outcome of children presented with poisoning in tertiary care hospital - Shah, Chirag D.; Kaple, Aditi; Pratihar, Kankana; Patel, Kush; Patel, Jhalak (International Journal of Contemporary Pediatrics, 2024)
Background: Poisoning is a common paediatric emergency. Worldwide estimate suggests that the rate of poisoning in under 20 years is 1.8 per one lakh population and for India it ranges between 0.6 to 11.6%. Methods: The study was conducted at B. J. Medical College Ahmedabad and Civil Hospital, Ahmedabad. A prospective analytical study consisting of total 110 patients, admitted in the intensive care unit during the period from June 2018 to November 2018 with inclusion criterion of children <12 years of age, presented with history of consumption of poisonous substances/insect bite irrespective of signs and symptoms excluding cases of food poisoning and idiosyncratic drug reactions. Detailed proforma was filled after taking necessary consent from the parents. Routine investigations and gastric samples for forensic analysis were sent in all irrespective of type or route of poisoning. Specific investigations done wherever required. Analysis of outcomes done using chi square. Results: The most common age group was 3-6 years with male to female ratio of 1.5:1. 99.1% poisoning were accidental with hydrocarbon poisoning being the most common of all (27.2%), followed by household substance poisoning in 20.9%. Snakebite was the most common insect bite (10.9%). The average duration of stay was 3.9 days, 8.1% children died with maximum mortality happened in children presented after 6 hours of intoxication. Conclusions: Management of poisoning requires immediate advice and first aid, followed by a directed treatment. Decontamination, enhanced elimination, antidotes, and supportive care are commonly used to manage poisoning cases.